Safeguarding the Future: Developing the Next Generation of Human Rights for Digital and Cognitive Domains - Marsili, M. (RC26 IPSA Interim Conference on Human Rights: The evolution of the position and role of human rights in political systems, 2024)
As we enter an era shaped by digital transformation, the concept of human rights is undergoing a profound shift. Traditional rights frameworks, originally designed for physical domains, face mounting pressure to adapt to the unique challenges posed by digitalization, artificial intelligence, cognitive warfare, and hybrid threats. This paper investigates the "next generations" of human rights, arguing that new principles are essential to protect individuals’ autonomy, privacy, and mental integrity in complex, digitally interconnected political environments. In a landscape where cognitive manipulation, misinformation, and cyber surveillance have become routine, emerging threats extend beyond physical security to influence mental and emotional well-being. This study explores how future-oriented human rights must evolve to include protections against psychological harm, cognitive exploitation, and loss of informational self-determination. By focusing on cognitive and psychological dimensions, it draws on contemporary research into cyber and information warfare, hybrid conflict, and manipulation in immersive digital environments like the metaverse. These environments blur the lines between reality and virtuality, making individuals increasingly vulnerable to subtle yet impactful forms of influence and control. Moreover, this paper examines the international legal and ethical frameworks required to address these emerging issues. Given that most current human rights norms predate the digital age, there is a need to update or expand these norms to reflect the complexity of today’s socio-political landscape. Drawing from studies on cognitive warfare and cybersecurity, the analysis highlights key areas where human rights protections can be reinforced or newly defined. These include rights to mental privacy, immunity from manipulation, and informational autonomy. Finally, the study considers the roles of national and global actors, suggesting that a multilateral, interdisciplinary approach is essential to effectively safeguard future generations of human rights. Governments, international organizations, and academic institutions will need to collaborate on policies that recognize and mitigate the risks associated with digital, cognitive, and hybrid forms of influence. Such collaboration can facilitate the development of adaptive, resilient human rights standards that anticipate and respond to the threats posed by rapidly advancing technology. This paper aims to contribute to a predictive model for the evolution of human rights, advocating for proactive measures that empower individuals within increasingly pervasive digital and hybrid domains. By proposing new frameworks, it calls for a holistic rethinking of human rights that aligns with contemporary and future geopolitical and technological realities.